Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family - Park, Kyu-Tek; Cho, Soowon; Bae, Yang-Seop (Zootaxa, 2016)
The Family Lecithoceridae of the Oceanian region, which includes New Guinea (Papua and Papua New Guinea) together with some islands east of Borneo and SW Pacific islands, is reviewed, with a description of Thubana brunalis Park, sp. nov. T. brunalis is the second species of the Torodorinae introduced to the region. Also included a historical review on the taxonomic works on the family in the region, a zoogeographical consideration of the taxa, and a tentative check list of the family, including 158 valid species names. Sphenocrates Meyrick, 1925, syn. nov. is synonymized with Crocanthes Meyrick. New combinations include Pectinimura palpella (Bradley, 1961), comb. nov. and Crocanthes neptis (Diakonoff, 1954), comb. nov.